Aerosol light absorption coefficients and black carbon concentrations at Neumayer for the year 2024 - Jurányi, Zsófia; Bösch, Tim (In: Jurányi, Zsófia; Weller, Rolf (2025): Aerosol light absorption coefficients and black carbon concentrations at Neumayer (2006 et seq) [dataset publication series]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.987702 (DOI registration in progress), 2025)
We operate a multi angle absorption photometer MAAP (Model 5012, Thermo Electron Corp.) in the Aerosol and Trace Gas Observatory at Neumayer III Station since March 2006 ongoing. This instrument measures the atmospheric aerosol light absorption coefficient (mainly caused by black carbon, BC) by sampling ambient aerosol glass fiber filter tape. The intake of the aerosol inlet can be found on top of the observatory at approx. 5-7 m above ground. The measured absorption coefficients abs(637) refer to a wavelength of 637 nm. Raw data were originally sampled in one-minute resolution. Finally, hourly averaged MAAP data are presented here. We also provide BC concentrations (ng/m³) derived from the absorption coefficients using the specific BC mass absoption coefficient of 6.6 m²/g.
Keywords: aerosol; aerosol absorption coefficient; black carbon; Neumayer Station; Spuso